DNA Tumor Viruses - Pipas, James.; Damania, Blossom. (Springer US, 2009)
The DNA tumor viruses are central to many branches of molecular and cellular biology. This very diverse group of viruses attack common cellular pathways, which makes them powerful tools for understanding how multiple complex pathways are integrated. Additionally, the unique mechanisms employed by each viral system to alter cellular functions serve as powerful molecular probes for the identification of new targets and pathways. The scientific impact of the DNA tumor viruses extends far beyond their etiologic role in human cancers, or their contributions to our basic understanding of the cellular pathways that drive tumorigenesis. Currently, research on these viruses lies at the interface of cancer and the innate and adaptive immune response, investigating how infectious agents influence, evade, and utilize systems that regulate these processes. Thus, DNA tumor viruses serve as models for the systems biology of host-pathogen interactions. "DNA Tumor Viruses," edited by Blossom Damania and James M. Pipas, summarizes recent advances in our understanding of this diverse and fascinating collection of viruses.